The revolutionary rhetoric of Olympe de Gouges. - Diamond, Marie Josephine (Feminist Issues)
This article analyzes the writings of Olympe de Gouges In the context of her inscription in Revolutionary discourse. It begins with her anti-slavery play The Slavery of Blacks, which appeals for the legitimation of both women and blacks; follows her early political pamphlets culminating in the extraordinary “Declaration of the Rights of Woman” (1791), an appeal for full civil and political rights for women (and disenfranchised men), and concludes with the desperate, accusatory letters to Robespierre and the pamphlet “The Three Urns,” which led her to the guillotine. Through a reading of her rhetoric, the article shows the stages of her writing and how she was increasingly marginalized and silenced by a discourse that finally excluded women from the public sphere. Reprinted by permission of the publisher.